Women, not objects: testing a sensitizing web campaign against female sexual objectification to temper sexual harassment and hostile sexism. Issue 4 (4th July 2021) - Guizzo, Francesca; Cadinu, Mara
ABSTRACT: We investigated the novel hypothesis that a sensitizing web campaign against media sexual objectification would lead to lower male gender-harassing conduct (i.e., number of sexist jokes sent to a chat partner), lower sexual coercion intention (via the Likelihood to Sexually Harass scale), and lower hostile sexism (via the Ambivalent Sexism Inventory). Across two experiments ( Ns = 157; 159), male participants were exposed to one of three videos: (a) a web campaign against female objectification (sensitizing), (b) a nature documentary (control), or (c) a video in which women are portrayed as sexual objects (sexually objectifying). Study 1 and Study 2 together demonstrated that men exposed to the sensitizing video showed lower gender-harassing behavior, lower hostile sexism, and lower sexual coercion intention than participants in the other two conditions altogether. Moreover, the sexually objectifying vs. control video condition led to higher gender-harassing behavior. Mediation analyses demonstrated that the sensitizing video led to lower hostile sexism, which in turn was associated with both lower gender-harassing behavior and lower sexual coercion intentions. The sensitizing video led to unexpectedly higher benevolent sexism; however, benevolent sexism was not associated with higher sexual harassment. We conclude by discussing the importance and practical implications of the results.